Effective and Efficient Cabinet as One of the Efforts to Prevent Corruption - Rico Septian Noor; Sri Endah Wahyuningsih (Universitas Bali Dwipa, 2023)
Corruption never seems to disappear in Indonesia, because almost every day there is news in various print and electronic media regarding public officials, legislative members and even law enforcers who are caught in corrupt practices. Therefore, more massive efforts are needed to prevent and eradicate corruption. This writing uses the Normative Juridical Research method which examines legal rules and principles in answering legal problems that occur using a Conceptual Approach to draw conclusions about the problems studied. We should all be aware that the moment of the General Election (Pemilu) is a very important moment considering the fact that 78 years of Indonesian independence is certainly a moment that must be interpreted deeply, the moment of forming an effective and efficient Cabinet is one of the determining factors for the success of the entire 5 Year government agenda. future and realizing the ideals of the Indonesian nation that have always been echoed, including realizing a government that is clean and free from corruption. Because the disease of corruption that has grown and taken root in this country is caused by many factors, one of which can be caused by the relationship between various systems that are related to corrupt cultural patterns in various functions of power in this country, for example co-optation and strong political intervention. This writing concludes that one of the important points in fixing various corruption problems is by repairing damage to the function and structure of government in this country. Forming an effective and efficient Cabinet in Government can be one of the keys to preventing Corruption